KAJI EKSPERIMENTAL PERFORMA PEMBAKARAN TUNGKU GASIFIKASI BIOMASSA TIPE TOP LIT UP-DRAFT PADA BERBAGAI KOMBINASI UKURAN BIOMASSA DAN KECEPATAN UDARA PRIMER AWAL - , EKO SURJADI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The technology development goes along with the increasing need for energy particularly the fossil one that is still relied on up to now while the availability of it is getting smaller. Particularly in the rural areas of Indonesia, the mean daily energy consumption per capita in the rural household is 25 MJ. The major activities consuming much energy are cooking about 95% and lighting about 5%. Thus, the renewable energy procurement should be carried out immediately. One way of doing so is to utilize the rice residue, hull of rice biomass, as the renewable energy with gasification technology. The objective of research is to obtain the combination of feed biomass size and prior primary air speed producing the highest output power in the Top Lit Up- Draft Type of Biomass Gasification Hearth. The experiment with Water Boiling test was done using hull of rice as the feed with varied sizes (2-4 mm, 5-7 mm, 10-11 mm, 25 mm, and 40 mm) and prior primary air speed between 2.4 and 3.8 m/s in the Top Lit Up-Draft Type of biomass gasification hearth. The data was obtained on start up time, operating time and total operating time of the use of Top Lit Up-Draft Type of Biomass Gasification Hearth with 600 gram feed biomass and 1 liter water. The result of research shows that the hull of rice biomass with the size below the hull of riceâs size (10-11mm) cannot provide combustion on the feed with the hearthâs prior primary air speed up to 3.8 m/s (maximum air speed of Top Lit Up- Draft Type of Biomass Gasification Hearth) meaning that the fissure between the biomasses which is so small that the resistance occurring is very high but with the size much less than 10% of hearth diameter (standard size of hull of rice biomass) can produce CH4 (methane) gas and can be used to boil water (100o) at air speed of 3.0 m/s and higher and the higher the prior primary air speed, the higher the output power up to the prior primary air speed of 3.8 m/s is 1.3302 kWatts while the stove efficiency of gasification hearth increases along with the increased prior primary air speed.